Creating a Unified Foundation for Generative Sustainable Development: Research, Practice and Education: the Perspective of a Development Economist and Practitioner. - Briganti, Arianna (European Journal of Sustainable Development, 2016)
This narrative unveils my own understanding of how to foster a unified foundation for generative sustainable development. I invite the reader to consider my insights into my practice as a development economist and practitioner who worked and lived in Afghanistan, Ethiopia, Georgia and currently in the Balkan region tackling sustainable development from the perspective of those at the receiving end of aid. By asking the beneficiaries from development interventions what sustainable development is, this journey aims also to communicate how my research is educational for my practical work in developing countries. My research is based on a methodology called Living Educational Theory (LT) that strengthens my ability to contribute to the establishment of the human capabilities of the people I work with in developing countries. Ultimately drawing from the evidence of both my work and research in practice I wish to clarify my own meaning of ’sustainable development’ and how this translates into a more holistic and value-based explanation of ’generative development’. The rise of generative development in relation to sustainable development is emerging from the synergy between LT and Development in practice, which results in a force that may drive human development and be conducive to a fairer world. Keywords: Sustainable Development, Human Development, Living Educational theory, Generativity